THE PROFILE OF BAMA BEACH BASED ON THE SUBSTRATE, THE PRESENCE OF SEAGRASS, CORAL LIFEFORM, AND ECHINODERMATA - Noorafebrianie Minarputri; Noer Moehammadi; Bambang Irawan (The East Java Biological Society, 2012)
Bama Beach is one of the most visited beaches in Baluran National Park, Situbondo. However, this beach does not have information of beach profile which is very important for managing coastal and marine resources. The aims of this research are to make beach profiles based on substrate, presence of seagrass, coral lifeforms, and Echinodermata. This research’s method is qualdrate transect. Five transects were made, roll meter pulled from the highest tides zone to the reef crest. The distance between each transect around 35–40 m. Plots 1x1 m2 were placed along each transect with 8-15 m gap between each plot. Geographical coordinates were noted for each plot so the results are data in those plots. The results are the dominant substrate in Bama Beach is sand and always mixed with gravel. Boulders specifically found in the highest tides zone and close to the reef crest. Seagrass can be found almost in all plots, about 10 to 250 m from the highest tides zone. The dominant coral lifeform on reef flat is coral submassive; then approaching the reef crest, the coral massive is the dominant one. At Bama Beach, was found 5 classes and 9 orders of Echinodermata. Asteroidea with order Valvatida and Spinulosida; Ophiuroidea with order Ophiurida; Echinoidea with order Camarodonta, Diadematoida, Stomopneustoida; Holothuroidea with order Aspidochirotida and Apodida; and Crinoidea with order Comatulida. Those orders live in all zones, which are sandy zone, seagrass zone, and coral reef zone.